Early Prevention Toward Sexual Abuse on Children - Ira Paramastri; - Supriyati; Muchammad A. Priyanto (Faculty of Psychology, Universitas Gadjah Mada, 2010)
Child sexual abuse is a worldwide problem. Although most studies on the longterm consequences of child sexual abuse have focused on women, sexual abuse of both boys and girls is common. Peer sexual abuse in schools was an often overlooked problem that contributes to a hostile school environment: one major study found that 85% of girls and 76% of boys reported experiencing some form of sexual abuse in school. 85% of child sexual abuse is committed by relatives, close family friend or an adult that the child knows and trusts. The childhood sexual abuse variables taken into account are commonly age of onset, duration, abuse forms and relationship between the child and the perpetrator. The objective of this study was to gather information or opinion about sexual abuse concept, methods and media of the elementary students, parents, teachers and experts. A qualitative study, involving one to one interviews, was conducted with 7 experts, focus group discussion with 40 elementary students, and with 40 parents in Yogyakarta district about child sexual abuse issues. Data were analysed according to Miles and Huberman’s data reduction, data display and conclusion verification process. These findings strongly indicate that boys and girls are vulnerable to this form of childhood sexual abuse ; the similarity in the likelihood for multiple behavioral, mental and social outcomes among men and women suggest the need to identify and treat all adults affected by child sexual abuse. Themes related to the child sexual abuse were: paperwork design, good facilitator, guidelines for students, parents and teachers. Students prefer media that can help them understand concept with komik paperwork as media for early prevention. Parents, teachers and experts prefer that this prevention program can run as soon. With careful paperwork design and evaluation of prevention program, the success of program implementation can be enhanced.